2017
DOI: 10.1007/s12672-017-0304-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Resveratrol Treatment Reduces the Risk of Mammary Carcinogenesis in Female Offspring Prenatally Exposure to 2,3,7,8-Tetrachlorodibenzo-p-Dioxin

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) presents adverse effects on breast development/carcinogenesis. This study aimed to identify the ability of resveratrol (Res) to modify the adverse effects of TCDD in a female offspring. Pregnant female Wistar rats were allocated into four groups: TCDD, TCDD + Res, Res, and control. TCDD (1 μg/kg) was orally administered as a single dose on gestational day (GD) 15, and Res was orally administered during GD10-21 and lactation at a dose of 20 mg/kg/day. Female offsprings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…125 Work is beginning on the ability of resveratrol exposure to pregnant rats to improve the health of their offspring, for example, to reduce the susceptibility of offspring to toxin-induced carcinogenesis. 126 And the protection provided by resveratrol against cancer is being traced, for example, to its ability at low concentrations to stabilize spindle assemblies during mitotic division of normally mitotic cells. 127 The horizons of study of resveratrol, indeed of all the resilience-inducing interventions considered here, continue to broaden.…”
Section: Foodmentioning
confidence: 99%
“…125 Work is beginning on the ability of resveratrol exposure to pregnant rats to improve the health of their offspring, for example, to reduce the susceptibility of offspring to toxin-induced carcinogenesis. 126 And the protection provided by resveratrol against cancer is being traced, for example, to its ability at low concentrations to stabilize spindle assemblies during mitotic division of normally mitotic cells. 127 The horizons of study of resveratrol, indeed of all the resilience-inducing interventions considered here, continue to broaden.…”
Section: Foodmentioning
confidence: 99%
“…Although the effects of oxidative stress caused by TCDD in the prostate were not excessively harmful during the study period, other studies point to an increase in the susceptibility to breast carcinogenesis [54], alteration in the stereogenesis and in the antioxidant system of epididymal sperm [81]. Adittionally, further studies can be proposed for an evaluation of the effects of gestational exposure to TCDD in older adult animals and in models of prostatic carcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, resveratrol is a polyphenolic compound with an AhR antagonist activity and that has anti-inflammatory, antioxidant and anti-cancer properties that might to inhibit TCDD adverse actions [49][50][51][52][53]. Some in vivo studies have shown that resveratrol can mitigate the toxic effects induced by in utero TCDD exposure in male and female reproductive organs, including reduction in breast cancer susceptibility [54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, resveratrol is able to synergistically enhance the effect of aromatase inhibitors on hormone-sensitive BC cells by modulating aromatase activity at the epigenetic level, sustaining the hypothesis of its co-therapeutic benefits [ 177 ]. Further, resveratrol also appears to be a promising natural substance for the prevention of BC recurrence during pregnancy, without negative effects on the embryo [ 178 ]. Indeed, positive effects of resveratrol on embryogenesis and the prevention of BC during pregnancy and pregnancy complications as well as on improvements in reproductive health have been reported [ 179 , 180 ].…”
Section: Resveratrolmentioning
confidence: 99%